Exponential Decline in the Dispersal of Stone Artefacts in Roman Britain: Further Expressions of Trade. Issue 1 (February 2015) - Allen, J.R.L.
Summary Several industries that exploited stone are known to have sprung up in Iron Age–Roman and Roman Britain. They include the fashioning of rotary querns from the Upper Old Red Sandstone of the Forest of Dean and the Lower Cretaceous Hythe Beds (Lodsworth rock) of West Sussex, the production of whetstones from sandstones in the Weald Clay Formation of the north‐west Weald, and the manufacture of a wide range of products from the Upper Jurassic Purbeck Marble of south‐east Dorset. The dispersal of goods from these sources is found to exhibit a similar exponential decline with distance to that previously demonstrated for prehistoric stone artefacts and Romano‐British ceramics. Evidently, interactions at settlements led to the retention of a roughly constant proportion of the goods brought there.